Commercial aviation and cyber security : a critical intersection - Koepsel, Kristen M. (SAE International, 2017)
As cyber attacks become more frequent at all levels, the commercial aviation industry is gearing up to respond accordingly. Commercial Aviation and Cyber Security: A Critical Intersection is a timely contribution to those responsible for keeping aircraft and infrastructure safe. It covers areas of vital interest such as aircraft communications, next-gen air transportation systems, the impact of the Internet of Things (IoT), regulations, the efforts being developed by the Federal Aviation Administration (FAA), and other regulatory bodies. The book also collects important information on the best practices already adopted by other industries such as utilities, defense and the National Highway Traffic Safety Administration in the US. It equally addresses risk management, response plans to cyber attacks, managing supply chains and their cyber-security flaws, personnel training, and the sharing of information among industry players. Commercial Aviation and Cyber Security: A Critical Intersection looks at possible future scenarios and how to respond to ever-growing cyber threats, how standards development will help combat this issue, listing the recommendations proposed by international agencies.--Provided by publisher.